2015
DOI: 10.1037/a0038655
|View full text |Cite
|
Sign up to set email alerts
|

Treating insomnia improves mood state, sleep, and functioning in bipolar disorder: A pilot randomized controlled trial.

Abstract: Objective To determine if a treatment for interepisode bipolar disorder I patients with insomnia improves mood state, sleep, and functioning. Method Alongside psychiatric care, interepisode bipolar disorder I participants with insomnia were randomly allocated to a bipolar disorder–specific modification of cognitive behavior therapy for insomnia (CBTI-BP; n = 30) or psychoeducation (PE; n = 28) as a comparison condition. Outcomes were assessed at baseline, the end of 8 sessions of treatment, and 6 months late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
172
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(183 citation statements)
references
References 64 publications
(101 reference statements)
6
172
0
5
Order By: Relevance
“…It further underscores the importance of hypersomnia in BD, which appears particularly relevant to BD I. Given that treatment of sleep disturbances may influence illness course in BD, providers should be mindful to assess and treat sleep disturbances in BD 5 6. Non-pharmacological approaches to hypersomnia treatment are sorely needed.…”
Section: Do These Results Change Your Practices and Why?mentioning
confidence: 99%
“…It further underscores the importance of hypersomnia in BD, which appears particularly relevant to BD I. Given that treatment of sleep disturbances may influence illness course in BD, providers should be mindful to assess and treat sleep disturbances in BD 5 6. Non-pharmacological approaches to hypersomnia treatment are sorely needed.…”
Section: Do These Results Change Your Practices and Why?mentioning
confidence: 99%
“…The study also showed that sleep irregularity might act as a risk factor for the prospective onset of major depressive episodes in bipolar disorder. A recent study showed that CBT-I was able to improve mood state, sleep, and functioning in bipolar disorder [36]. Further studies are needed to examine whether CBT-I can also reduce sleep irregularity and subsequently improve the outcome of bipolar disorder.…”
Section: Discussionmentioning
confidence: 98%
“…Empirically supported treatments that address sleep quality in BPI have demonstrated considerable promise in reducing the number and severity of mood episodes [5]. Research focused on identifying individuals at high risk for sleep disturbances, and specific mechanisms related to sleep quality may allow for future development of an early detection and intervention program to attenuate the risk of the onset of a mood episode.…”
Section: Discussionmentioning
confidence: 99%
“…BPI manic episodes are characterized by sleep disturbances including "decreased need for sleep," while depressive episodes are characterized by "changes in sleep" and "fatigue or loss of energy" [4]. Accordingly, recent research has focused on sleep-specific interventions to reduce the risk of relapse in people with BPI [5]. A modified form of cognitive behavioral therapy for insomnia has been shown to be effective for reducing the hypomania/mania relapse rate, reducing the number of days in a bipolar episode, and early data suggest it may even lower the overall mood episode relapse rate [5].…”
Section: A Preliminary Study Of Central Nervous System Arousal and Slmentioning
confidence: 99%